A review on landfill system for municipal solid wastes: Insight into leachate, gas emissions, environmental and economic analysis. (December 2022) - Yaashikaa, P.R.; Kumar, Ponnusamy Senthil; Nhung, Tran Cam; Hemavathy, R.V.; Jawahar, Marie Jyotsna; Neshaanthini, J.P.; Rangasamy, Gayathri
Abstract: Landfill is one of the common processes for removing and disposing waste materials that comprises the final method of disposing municipal solid waste. Disposal of municipal solid waste through land filling has become an important environmental problem all over the world which results in environmental contamination and pollution. Microbes present in the land act on the dumped materials and decompose the organic content present. The leachate from landfill is rich in organic, inorganic and suspended particles which may cause threat to ecosystem. The pollutants from leachate may be heavy metals, organic and inorganic content and organic compounds. The geological properties of soil get altered when leachate migrates. The physical, chemical and biological properties of the dumped material are determined by the decomposition of substances and microbes acting onto it. Trace gas emission may occur due to volatilization of chemical substances, degradation of waste materials and conversion reactions. The concentration of gas released varies from region to region of dumping, covered and uncovered dumped materials. The current review recommends an engineered landfill design helpful for landfill gas generation which replaces the fossil fuel as a compressed natural gas or liquefied natural gas. The landfill area is separated into organic and inorganic cells to scope at the objective of energy generation and resource recovery. However, the impact of these released gaseous emissions has been analyzed completely. Highlights: The generation of gas from the landfill is depends on the characteristics of MSW. Landfilling of MSW can produce landfill gas as a renewable energy. Control measures to limit the emissions from landfill sites are analyzed. Integrated bioreactor landfill for power generation has been discussed.